Profiling Critical Thinking Disposition and Preliminary Psychometric Evidence among Early-Year Science Education Students - Ni Nyoman Sri Putu Verawati; Wahyudi Wahyudi; Nina Nisrina (Universitas Pendidikan Mandalika, 2026)
This study profiled the critical thinking disposition of early-year science education students and examined preliminary psychometric evidence of an Ennis-based questionnaire. A quantitative descriptive survey with preliminary psychometric analysis was conducted with 90 second-semester science education students from three universities in West Nusa Tenggara Province, Indonesia. Data were collected using a 36-item questionnaire organized into 12 indicators of critical thinking disposition. Negatively worded items were reverse-scored before analysis. Descriptive statistics, category distribution, indicator-based profiling, Cronbach’s alpha, corrected item-total correlation, and exploratory factor analysis based on 12 indicator scores were applied. The results showed that students’ critical thinking disposition was generally moderate, with nearly all participants located in the moderate category. The highest indicator scores were found in precision required by situation, total situation, and employing critical thinking abilities, while the lowest scores were found in clear reasons, credible sources and observations, and being well-informed. The corrected internal consistency was modest, and several negatively worded items showed weak item-total correlations. The exploratory factor analysis suggested a tentative three-factor structure: evidence-based reasoning disposition, contextual and reflective judgment, and self-regulated critical engagement. These findings indicate that students’ critical thinking disposition is still developing and that the questionnaire requires further refinement.